Exploring of Teachers’ Beliefs on Teaching English at State Elementary Schools - REZKI; Chairil Anwar Korompot; Sukardi Weda (Program Studi Magister Pendidikan Bahasa Inggris, Fakultas Bahasa dan Sastra- Universitas Negeri Makassar., 2025)
This study aims to determine teachers' beliefs about teaching English at State Elementary Schools and the factors that shape teachers' beliefs about teaching English in State Elementary Schools. The type of research used in this study is qualitative descriptive research with the research subjects of English teachers in five State Elementary Schools in Polewali Mandar who teach English. The instruments used in this study were checklist observations, interviews, and documentation. The findings of the study indicate that teachers' beliefs about teaching English at State Elementary Schools that teach English in Polewali Mandar are predominantly using Body Movement Techniques to help these Elementary School children understand English vocabulary or commonly called the TPR (Total Physical Response) method. Teachers also have the belief that to teach English to Elementary School children is to use the PPP (Presentation, Practice, and Production) method, the next belief is that teachers carry out learning using the CLT (Communicative Language Teaching) method. The results of the study also show that there are two factors that shape teachers' beliefs about teaching English in five State Elementary Schools that teach English in Polewali Mandar. Both factors are in accordance with the theory of teacher cognition postulated by Borg (2006), two factors that are in accordance with this theory are the Schooling factor and the Classroom factor. Researchers did not find any other factors that shape the teacher's beliefs. The beliefs of these teachers are easily adjusted to the classroom context for the current elementary school level and there are no limitations to applying these beliefs to their classroom teaching practices, or there is no difference between teaching practices and the teacher's beliefs. Keyword: Teachers’ Beliefs, Factor’s Teachers’ Beliefs, Teaching English